2023
DOI: 10.3390/healthcare11050643
|View full text |Cite
|
Sign up to set email alerts
|

Functional Improvement and Satisfaction with a Wearable Hip Exoskeleton in Community-Living Adults

Abstract: Demand for wearable devices and supportive technology is growing as these devices have the potential to enhance physical function and quality of life in users. The purpose of this study was to investigate usability and satisfaction after performing functional and gait exercise with a wearable hip exoskeleton in community-living adults. A total of 225 adults residing in the local community participated in this study. All participants performed 40 min of exercise once with a wearable hip exoskeleton in various e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 37 publications
0
0
0
Order By: Relevance
“…To explore the opportunities, challenges, issues, and bottlenecks of integrating these tools (alone or interconnected) into the domain, this Special Issue [10] was initiated in May 2022, and was subsequently completed in January 2023. This Special Issue collected 17 contributions plus an editorial [1,[11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27], and covered a wide range of topics, including:…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…To explore the opportunities, challenges, issues, and bottlenecks of integrating these tools (alone or interconnected) into the domain, this Special Issue [10] was initiated in May 2022, and was subsequently completed in January 2023. This Special Issue collected 17 contributions plus an editorial [1,[11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27], and covered a wide range of topics, including:…”
mentioning
confidence: 99%
“…Kim et al [12] investigated enhancing usability and satisfaction among adults in community living through functional and gait exercises utilizing a wearable hip exoskeleton. They showed that a single session of exercise with this tool allowed an improvement in performance of both middle-and old-aged adults.…”
mentioning
confidence: 99%
See 1 more Smart Citation